Vascular Protection of Hydrogen Sulfide on Cerebral Ischemia/Reperfusion Injury in Rats - Wen, Ji-Yue; Wang, Mei; Li, Ya-Nan; Jiang, Hui-Hui; Sun, Xuan-Jun; Chen, Zhi-Wu (Frontiers in Neurology, 2018)
This study was undertaken to demonstrate the vascular protection of exogenous and endogenous hydrogen sulfide (H2S) on cerebral ischemia/reperfusion (I/R) injury. The effect of H2S on cerebrovascular dysfunction in middle cerebral artery (MCA) and neuronal damage were measured after cerebral I/R induced by transient middle cerebral artery occlusion (MCAO) in cystathionine c-lyase (CSE) knockdown and wild-type rats. The effect of sodium hydrosulfide (NaHS, donor of exogenous H2S), L-cysteine (L-Cys, substrate of endogenous H2S), and endothelium cells on the responses of isolated MCA derived from non-ischemic rats was also evaluated to assess the underlying mechanism of H2S-mediate cerebral vasodilation. The results revealed that the contraction and dilation of MCA profoundly decreased after cerebral I/R. The vascular dysfunction became more grievous in CSE knockdown rats than in wild-type rats. Interestingly, this vascular dysfunction was significantly alleviated by NaHS supplementation. Moreover, both NaHS and L-cysteine could induce remarkable relaxation in the isolated MCA, which was eliminated by co-application of potassium channel blockers ChTx and Apamin, or endothelial removal. By contrast, adding endothelium cells cultured in vitro together with ACh into the luminal perfusate could mimic non-NO and non-PGI2 relaxation in endothelium-denuded MCA, once CSE was knocked down from endothelium cells, and its effect on vasorelaxation was abolished. Furthermore, the indexes of neuronal injury were measured after cerebral I/R to confirm the neuroprotection of H2S, and we found that the neurological scores, cerebral infarction volume, brain water content, malondialdehyde content, and serum lactate dehydrogenase activity (a marker of cellular membrane integrity) were significantly higher in CSE knockdown rats than in normal control rats. It is not surprising that NaHS could alleviate the cerebral injury. These findings revealed that H2S has a protective effect on cerebral I/R injury via its upregulation of the endothelium-dependent contraction and dilation function of cerebral vessels, which may be related to activating potassium channel.